Thaharah dalam Perspektif Al-Qur`an: Fondasi Kebersihan Jasmani dan Rohani Muslim serta Membangun Budaya Bersih - Cintana Balkis Habibah; Aditya, Tiara Dewinta; Assyifa Azzahra; Triana Srisantyorini; Ayunda Larasati Sekarputri; Andriyani (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
Thaharah represents a core principle within Islamic teachings, encompasses both bodily cleanliness and spiritual sanctity, and functions as an essential requirement for the proper observance of acts of worship, including prayer, tawaf, and the recitation of the Qur’an. This concept extends beyond ritual practice, reflecting a manifestation of faith that encourages Muslims to maintain personal hygiene, environmental cleanliness, and spiritual closeness to Allah SWT. This study aims to explore and critically examine the concept of thaharah in a comprehensive manner, clarify its role within Islamic religious practices, and assess its relevance in fostering clean lifestyle behaviors and appropriate worship practices in accordance with Islamic legal principles in contemporary society. Conceptually, thaharah is divided into two main forms: purification from ritual impurity (hadas) through ablution (wudu), ritual bathing (ghusl), or dry purification (tayammum), and purification from physical impurities (najis) by cleansing the body, clothing, and surrounding environment. The normative foundation of thaharah is reinforced by textual evidence, including Surah Al-Ma’idah verse 6 and prophetic traditions that emphasize cleanliness as an integral part of faith. Thus, thaharah offers a holistic perspective on cleanliness that integrates both worldly and spiritual dimensions of Muslim life.